1989
DOI: 10.1177/014860718901300159
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Diethylhexylphthalate from Total Nutrient Solution‐Containing Polyvinyl Chloride Bags

Abstract: Total nutrient solution (TNS) is a new method for delivering total parenteral nutrition (TPN) by admixing dextrose, amino acids, and lipids in a single container. Recommendations are to use nonpolyvinyl chloride (PVC) containers for admixture of these solutions. PVC is a hard, brittle, and inflexible substance, and plasticizers, predominantly diethylhexylphthalate (DEHP), are added to impart flexibility. DEHP is a lipid soluble suspected carcinogen, hepatotoxin, and teratogen which has been shown to leach from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Di(2‐ethylhexyl) phthalate has limited solubility in aqueous solutions (approximately 3 ng.ml −1 in distilled water at 20 °C [28]), but is non‐covalently bound to PVC, so will leach into an aqueous solution at higher temperatures [29] and during the mechanical stress associated with dynamic flow [30]. The lipophilicity of DEHP explains the greater rate of leaching into lipid‐containing solutions [12], and may also be affected by other factors, including the length and volume of the infusion line, infusate pH, infusion duration, plasticity and agitation of the PVC equipment [31].…”
Section: Discussionmentioning
confidence: 99%
“…Di(2‐ethylhexyl) phthalate has limited solubility in aqueous solutions (approximately 3 ng.ml −1 in distilled water at 20 °C [28]), but is non‐covalently bound to PVC, so will leach into an aqueous solution at higher temperatures [29] and during the mechanical stress associated with dynamic flow [30]. The lipophilicity of DEHP explains the greater rate of leaching into lipid‐containing solutions [12], and may also be affected by other factors, including the length and volume of the infusion line, infusate pH, infusion duration, plasticity and agitation of the PVC equipment [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that as DEHP is not chemically bound to PVC, it leaches out from medical products into the media, which comes in contact with it 6–9. There is mounting concern for the exposure to the phthalate ester through various medical procedures such as intravenous therapy, enteral and parenteral nutrition support, blood transfusion, hemodialysis and peritoneal dialysis, cardiopulmonary bypass, and extracorporeal membrane oxygenation 10–13. Although DEHP is suggested to be of low acute toxicity, long‐term exposure may adversely affect the human being 14.…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing medical procedures, such as intravenous therapy, nutritional support, blood transfusion, hemodialysis, cardiopulmonary bypass or extracorporeal membrane oxygenation (EMO) can be exposed to DEHP. Previous studies have shown detectable amounts of DEHP in blood products, in intravenous solutions, and in intravenous fat emulsions stored in PVC bags [1][2][3][4][5]. In animal studies, DEHP and/or MEHP are toxicants to the reproductive and developmental systems [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%